Transitions in the thermal stability of pre-strained austenite – competing effects between defect density and slip band spacing. (15th January 2023) - Dong, Guangqi; Wang, Jinliang; Wang, Lingyu; Wang, Chenchong; Hu, Jun; Xu, Wei
Abstract: The transition from mechanical destabilization to stabilization in metastable austenite is an important issue affecting the design of structures used at lower temperatures. We have conducted in-situ magnetic measurement and detailed microscopy work to reveal the underlying mechanisms of such transition. Austenite destabilization is attributed to the increase of slip band and dislocation densities which provide extra nucleation sites. The decreased slip band spacing divides the austenite grains into small units, hindering the growth of martensite. It also inhibits the formation of multiple martensite variants and retards nucleation. The competition between defect density and spacing is the key to the transition. Graphical abstract: Image, graphical abstract